Three pathways to better recognize the expertise of Global South researchers - Nakamura, Gabriel; Soares, Bruno Eleres; Pillar, Valério D.; Diniz-Filho, José Alexandre Felizola; Duarte, Leandro (Npj Biodiversity, 2023)
It is widely perceived how research institutes have been adopting the discourse of champions of diversity, inclusion, and equity (DEI) in recent years. Despite progress in diversity and inclusion in the academic environment, we highlight here that nothing or, at very best, little work has been done to overcome the scientific labor division in academic research that promotes neocolonial practices in academic recognition and jeopardizes equity. In this piece, we bring secondary data that reinforce biased patterns in academic recognition between Global North and South (geographical markers and citation bias), and propose three actions that should be adopted by researchers, research institutes, journals, and scientific societies from the Global North that allows for a fairer recognition of the academic expertise produced by the Global South.